(untitled) (Journal of Science and Technology Research, 2024)
Revealing electronically excited states across organic/organic interfaces is important to speculate the charge photo-generation mechanisms in organic devices. As organic solar cells are large and unorganized systems so it is very tough to access it using conventional quantum chemical approaches. To unearth the charge separation mechanism a massive scale of excited states should be considered. For this purpose in this study, we have applied recently developed fragment molecular orbital (FMO) method that can effectively consider large-scale molecular aggregates. In our model, we have treated for different configurations of pentacene/C60 bilayer hetero-junction structures. Here, we have also discussed the charge delocalization effect, structural deformations. The measured energy dynamics low-lying interfacial CT states are in well match with experimental reports. J. of Sci. and Tech. Res. 5(1): 169-178, 2023